2014
DOI: 10.1073/pnas.1320952111
|View full text |Cite
|
Sign up to set email alerts
|

HNH proteins are a widespread component of phage DNA packaging machines

Abstract: The genome packaging reactions of tailed bacteriophages and herpes viruses require the activity of a terminase enzyme, which is comprised of large and small subunits. Phage genomes are replicated as linear concatemers composed of multiple copies of the genome joined end to end. As the terminase enzyme packages the genome into the phage capsid, it cleaves the DNA into single genome-length units. In this work, we show that the phage HK97 HNH protein, gp74, is required for the specific endonuclease activity of HK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 35 publications
4
106
1
Order By: Relevance
“…HNH motifcontaining endonuclease proteins may interact with phage terminase proteins to promote phage DNA packaging and maturation (31). For example, a recent report showed that gp74 (an HNH endonuclease) of phage HK97 interacts with its terminase protein (32) and that the HNH motif of endonuclease is essential for interacting with terminase and completion of DNA packaging. Also, lambda gpFI, an endonuclease, interacts with lambda terminase (16).…”
Section: Discussionmentioning
confidence: 99%
“…HNH motifcontaining endonuclease proteins may interact with phage terminase proteins to promote phage DNA packaging and maturation (31). For example, a recent report showed that gp74 (an HNH endonuclease) of phage HK97 interacts with its terminase protein (32) and that the HNH motif of endonuclease is essential for interacting with terminase and completion of DNA packaging. Also, lambda gpFI, an endonuclease, interacts with lambda terminase (16).…”
Section: Discussionmentioning
confidence: 99%
“…Another HNHE, gp74 was discovered from E. coli phage HK97 that cleaves λ DNA into small fragments in Ni 2+ or Zn 2+ buffer (26,27). Gp74 was shown to be associated with HK97 terminase large and small subunits (TerL/S) complex and stimulated cleavage/nicking at the cohesive end site (cos) (28). It was speculated that TerL-S enzyme may cleave one strand and gp74 may nick the opposite strand.…”
Section: Naturally Occurring Hnhe Associated With Bacterial Mobile Gementioning
confidence: 99%
“…It was convincingly demonstrated that gp74 was involved in DNA packaging and morphogenesis since HK97 gp74 amber mutant (74am) produced only empty prohead, but generated normal tails structures that can complement tail-deficient mutants. Furthermore, gp74 amber phage can be rescued by in vivo complementation when gp74 is provided in trans from a plasmid (28). To analyze the cleavage/nicking sites of gp74, we expressed and purified gp74 (see Supplementary Material).…”
Section: Naturally Occurring Hnhe Associated With Bacterial Mobile Gementioning
confidence: 99%
“…This mechanism was confirmed recently for Microplitis demolitor BV (MdBV) by inactivation of two nudiviruslike tyrosine recombinase genes (Vlf1 and Int-1) using RNA interference, which indeed resulted in impairment of circle formation [18 ]. Circularization probably occurs in combination with entry of replicated DNA into the nucleocapsids [7], as found for many viruses for which concatemers of genomes produced during DNA replication are separated during encapsidation (for example phages [34] and herpesviruses [35]). …”
Section: Chromosomal Amplification (Drosophila Chorion Genes «Onion Smentioning
confidence: 56%